(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
This article outlines the technology, biology, ecology, importance and chemical composition of amaranta growth in agriculture and agriculture. Although the name is unfamiliar to many, the treatment characteristics of the amaranth plant are known in medicine